2004
DOI: 10.1002/rem.20024
|View full text |Cite
|
Sign up to set email alerts
|

Study of the future land use of a contaminated site: Preferences versus potential use

Abstract: Worldwide, agencies with high levels of contamination are faced with decisions about remediation and restoration. These decisions should be informed by future land use and long-term stewardship goals. In the United States, the Department of Energy has lands in some 34 states that require cleanup. They are involved in massive remediation and restoration efforts on lands from the Cold War legacy and wish to reduce their overall footprint. Understanding future land use preferences is essential for determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Two of these studies utilized structured interviews and found that future land use preferences differed by ethnicity, with participants that were members of the Shoshone Bannock tribe (Idaho) rating camping, fishing, hunting, and returning the land to Native people higher than white participants did. Native American participants were generally underrepresented, however, in both studies (324 out of 1370 participants (23.6%) and 11 out of 254 participants (3.5%)) (Burger, 2004a, 2004b). Another study involving semi-structured interviews of 18 members of the Dene and Metis communities of Fort Resolution (Northwest Territories) found that since the establishment and closing of the Abandoned Pine Point Mine site, the community’s land use patterns had changed from a land-based economy to a mixed economy reliant on wage labor, concluding that post-remediation land use would likely be different than land uses before the site’s establishment (LeClerc & Keeling, 2015).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Two of these studies utilized structured interviews and found that future land use preferences differed by ethnicity, with participants that were members of the Shoshone Bannock tribe (Idaho) rating camping, fishing, hunting, and returning the land to Native people higher than white participants did. Native American participants were generally underrepresented, however, in both studies (324 out of 1370 participants (23.6%) and 11 out of 254 participants (3.5%)) (Burger, 2004a, 2004b). Another study involving semi-structured interviews of 18 members of the Dene and Metis communities of Fort Resolution (Northwest Territories) found that since the establishment and closing of the Abandoned Pine Point Mine site, the community’s land use patterns had changed from a land-based economy to a mixed economy reliant on wage labor, concluding that post-remediation land use would likely be different than land uses before the site’s establishment (LeClerc & Keeling, 2015).…”
Section: Resultsmentioning
confidence: 83%
“…Native American participants were generally underrepresented, however, in both studies (324 out of 1370 participants (23.6%) and 11 out of 254 participants (3.5%)) (Burger, 2004a(Burger, , 2004b.…”
Section: Long-term Managementmentioning
confidence: 80%
See 1 more Smart Citation
“…Many of today's waste management techniques do not eliminate contaminants, such as hazardous and radioactive waste, but rather only concentrate and/or attempt to contain the contaminants of concern (Applegate & Dycus, 1998;NRC, 1997;Rumer & Mitchell, 1995;Russell, 2000;Suter, Luxmoore, & Smith, 1993;US EPA, 1998). Remedial decisions concerning these complex challenges often focus on mitigation actions to reduce risk (Burger, 2004b;Greenberg et al, 2002;Mayer, Faass, Greenberg, & Lewis, 2006). However, risks to human health and the environment frequently remain at many sites even after regulatory-approved environmental remediation operations are complete (US DOE, 1997DOE, , 1999DOE, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Although this range of options was constrained in Bayonne to residential versus commercial, the full range does exist in many other places, including, in our experience, at the Department of Energy sites. 29,30 It is the iterative nature of what the Department of Energy calls risk-based end states that imposes a challenge to integrate risk management, engineering, and economics. 3 The robustness of the remediation management to the dynamics of a negotiated understanding of the desired end state to the resident population concerns and to the discovery of unexpected contamination were all a direct consequence of the adherence to risk-based principles.…”
mentioning
confidence: 99%